Moda Transportasi Angkutan Kota Berbasis Teknologi Informasi Komunikasi - Aisah Tri Wahyuni; Rini Rachmawati (Institut Transportasi dan Logistik Trisakti, 2019)
Utilization of Information and Communication Technology (ICT) in the field of transportation has an important role in meeting the needs of the community. Bogor is one of the cities that have developed public transportation modes by utilizing ICT to improve community services, namely modern Para transit. This study aims to understand various modes of public transportation, the operation of modern public transportation, and the needs of the community for modern public transportation in the city of Bogor. The results showe that conventional Para transits and Trans Pakuan Buses experienced a decline in the quality and interest of the community. Modern public transportation comes with ICT facilities as an innovation to overcome these transportation problems and traffic congestion through the re-routing program. Modern public transportation has not been able to operate fully, but during the trial phase it actually caused opposition from several parties, consequently, it currently stops operating and has not fully met the needs of the public transportation modes expected by the people of Bogor City.